2000
DOI: 10.1096/fj.00-0162
|View full text |Cite
|
Sign up to set email alerts
|

Leptin promotes invasiveness of kidney and colonic epithelial cells via phosphoinositide 3‐kinase‐, Rho‐, and Rac‐dependent signaling pathways

Abstract: Leptin plays a key role regulating food intake, body weight and fat mass. These critical parameters are associated with an increased risk for digestive and mammary gland cancer in the Western population. Here we determined whether leptin contributes to the invasive phenotype of colonic and kidney epithelial cells at various stages of the neoplastic progression. First, leptin potently (EC50 = 10-30 ng/ml) induces invasion of collagen gels by premalignant familial adenomatous colonic cells PC/AA/C1 and nontumori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
200
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(217 citation statements)
references
References 55 publications
14
200
1
2
Order By: Relevance
“…Rac1 mediates a number of adhesionand growth factor-dependent responses, including the membrane ruffling and lamellipodia formation that function in the advancement of the leading edge of migrating cells (Hall, 1998). Accordingly, we found that MDCKT23-Rac1V12 cells expressing the constitutive activated form of Rac1 (Jou and Nelson, 1998) are invasive without the addition of stimulators (Attoub et al, 2000). The involvement of the Rho signaling pathway in cellular invasion induced by BA was confirmed by our data using the pharmacological inhibitors of the Rho GTPases (C3T exoenzyme) and its downstream effector, ROCK (Y27632).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Rac1 mediates a number of adhesionand growth factor-dependent responses, including the membrane ruffling and lamellipodia formation that function in the advancement of the leading edge of migrating cells (Hall, 1998). Accordingly, we found that MDCKT23-Rac1V12 cells expressing the constitutive activated form of Rac1 (Jou and Nelson, 1998) are invasive without the addition of stimulators (Attoub et al, 2000). The involvement of the Rho signaling pathway in cellular invasion induced by BA was confirmed by our data using the pharmacological inhibitors of the Rho GTPases (C3T exoenzyme) and its downstream effector, ROCK (Y27632).…”
Section: Discussionmentioning
confidence: 90%
“…Invasion and metastasis, the hallmarks of malignant tumors, are both greatly influenced by autocrine, paracrine and endocrine factors in the tumor (Mareel et al, 1996). Accordingly, invasion of colorectal cancer cells into collagen type I is induced by endogenous factors, such as hepatocyte growth factor (HGF), leptin and trefoil peptides (Empereur et al, 1997;Kotelevets et al, 1998;Attoub et al, 2000;Emami et al, 2001). The possible implication of BA in cancer cell invasion is suggested by the correlation between Dukes' stage of human colon tumors, and abnormal fecal deoxycholic acid (DCA)/ cholic acid (CA) and LCA/DCA concentration ratios, as well as the number of the BA binding sites in tumor cells (Summerton et al, 1983;Owen, 1997;Kamano et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of Rac in cell invasion has been established in several experimental systems (59 -62). The overexpression of activated Rac1 promotes the invasion of some carcinoma cell lines in collagen (59,63), whereas the dominant negative forms of Rac1 inhibit leptinstimulated cell invasion in collagen gels (60), implicating Rac1-dependent pathways in epithelial cell invasion. However, activated Rac also promotes enhanced cell-cell junction assembly in MDCK cells (64), inhibiting their dispersal in response to HGF (65,66).…”
Section: Mek1-dependent Signals Synergize With Crkii To Promote the Lmentioning
confidence: 99%
“…Recently, inhibition of motility or invasion by rapamycin has been described in porcine, murine and human aortic smooth muscle cells (Poon et al, 1996;Sun et al, 2001;Sakakibara et al, 2005), canine kidney epithelial cells (MDCKT23) and human colorectal cells (HCT-8/ S11) (Attoub et al, 2000), Swiss 3T3 fibroblasts (Berven et al, 2004), trophoblast (SGHPL-4) (Cartwright et al, 2002), neutrophils (Gomez-Cambronero, 2003), ovarian cells (Wong et al, 2004), and human umbilical vein endothelial cells (Kwon et al, 2005) in culture. In vivo, rapamycin also potently inhibits metastases of transplanted tumors derived from murine adenocarcinoma cells (CT-26) (Guba et al, 2002), human renal cancer cells (RCC 786-O) (Luan et al, 2003), murine nonsmall-cell lung cancer cells (KLN-205) (Boffa et al, 2004) and osteosarcoma (K7M2) (Wan et al, 2005) in mice.…”
Section: Introductionmentioning
confidence: 99%